(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Iliotibial band (ITB) tightness affects 12.8-45.69% of Pakistani urban populations and 5-14% of runners internationally, causing lateral knee pain and patellar Maltracking through excessive friction (400-600N at 30° knee flexion. Limited RCTs compare isolated ITB stretching versus Myofascial release (MFR). Objective: To evaluate comparative effectiveness of ITB stretching versus MFR for ITB extensibility and patellar tracking correction among runners/athletes with ITBS. Methods Double-blind parallel RCT (N=120; 60/arm) in Karachi clinics following CONSORT guidelines.  Participants (18-40 years, Ober’s <50°, VAS ≥4/10) Randomized to: (1) stretching (30s × 5 reps, 3x/day) (2) MFR (90s × 3 sets, 3x/day) for 4 weeks.  Primary: Ober’s test at 4 weeks.  Secondary: Patellar tracking (ultrasound) VAS, LEFS at 4/12 weeks. Intention-to-treat ANOVA α=0.05. Results: Baseline equivalence confirmed. MFR superior: Ober’s +9.2°±4.1° vs +6.4°±3.2° (p=0.007, d=0.78); patellar tracking normalized 72% vs 55% (p=0.04); VAS -4.7 vs -3.9 (p=0.04); LEFS +22.4 vs +18.2 (p=0.03). 12-week retention: 82% vs 68% (p=0.04). Attrition 8%. Conclusion: MFR demonstrated significantly greater improvements in ITB extensibility, pain reduction, patellar tracking, and functional outcomes compared to stretching. These findings support the potential role of MFR as an effective intervention for ITBS management; however, further large-scale and multicenter trials are recommended to confirm these results and enhance generalizability.